(3GdQJHI GdYdjG aj COH GdaJjGs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3gPG LRA hQOJ ajg GdCMGOjK hGdBKGQ GdhGQOI ai COH GdeaJi djYJeOg GdeUhf hdG jYJHQ GdYjhf s
(3BNQgG (B:s
(3ajbhdhf eGPG fJefi QHfG ajbhdhf JefhG cPG hcPG age jMJGLhf Edjge ai GdLfI ceG JMJGLhf Edjge ai GdOfjG hddg GdMeO BNQ GdQJHI GdYdjG ai BOGH GdaJjG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B128 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B534s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(1027(3d(B) s
Keywords: (3GdMOjK h GdeUWdMs